The Pros and the Cons for the Use of Silybin-Rich Oral Formulations in Treatment of Liver Damage (NAFLD in Particular) - Rosso, Natalia; Marin, Veronica; Giordani, Antonio; Persiani, Stefano; Sala, Federica; Cavicchioli, Lucio; C. Rovati, Lucio; Tiribelli, Claudio (Current Medicinal Chemistry, 2015)
The increasing prevalence of Non-Alcoholic Fatty Liver Disease (NAFLD) worldwide is becoming a challenge for the modern global care system. The lipotoxic process is characterized by an oxidative stress followed by a burst of the inflammatory response, prompting the wound healing process (fibrosis), which can ultimately lead to the development of cirrhosis and the subsequent complications. There is no consensus concerning an effective pharmacological treatment. Therefore, there is a need for effective therapeutic compounds. Silibinin the major active compound of Milk Thistle may be a potential candidate mainly due to its anti-oxidant, anti-inflammatory, and anti-fibrotic properties. In spite of the large number of data obtained in experimental models, the translation of the evidence in clinical setting is far to be conclusive. The aim of this paper is to critically review the aspects of the use of the different formulations of Silibinin in several experimental and clinical settings and to provide hints on the needed future studies.
Keywords: insulin resistance oxidative-stress